Gels as Promising Delivery Systems: Physicochemical Property Characterization and Recent Applications - Enzhao Wang; Zhaoying Qi; Yuzhou Cao; Ruixiang Li; Jing Wu; Rongshuang Tang; Yi Gao; Ruofei Du; Minchen Liu (Pharmaceutics)
Gels constitute a versatile class of materials with considerable potential for applications in both technical and medical domains. Physicochemical property characterization is a critical evaluation method for gels. Common characterization techniques include pH measurement, structural analysis, mechanical property assessment, rheological analysis, and phase transition studies, among others. While numerous research articles report characterization results, few reviews comprehensively summarize the appropriate numerical ranges for these properties. This lack of standardization complicates harmonized evaluation methods and hinders direct comparisons between different gels. To address this gap, it is essential to systematically investigate characterization methods and analyze data from the extensive body of literature on gels. In this review, we provide a comprehensive summary of general characterization methods and present a detailed analysis of gel characterization data to support future research and promote standardized evaluation protocols.